ANALISIS PENGARUH PERAN KEPEMIMPINAN TERHADAP KEPUASAN KERJA CV. MEKAR LESTARI - Suherman, Enjang (LPPM Universitas Buana Perjuangan Karawang, 2015)
ABSTRACT This research aims at analyzing the influence of role leadership, toward employee job satisfaction,. The proposed hypotheses: The role leadership have significance influence to the employee’s job satisfaction. The result of the research has evidenced that role leadership is significantly influence to the employee’s job satisfaction. And the conclution is that The role leadership has significance influence to the employee’s job satisfaction. Keyword: Role leadership, , Job satisfaction